Analysis of Production Cost Efficiency Strategy to Increase MSME Profits Through Target Costing Model in the Coastal Area of Bintan - Ronia Tambunan; Putri Yuliandari; Siti Arita Novia (Jurnal Informatika Ekonomi Bisnis, 2026)
This study aims to analyze the effect of cost efficiency strategies on profit improvement through the application of the target costing model among micro, small, and medium enterprises (MSMEs) engaged in seafood processing in the coastal region of Bintan Regency. The main challenges faced by coastal MSMEs include high raw material costs, limited cost control mechanisms, and the absence of systematic cost planning aligned with target profit objectives. This research employs a quantitative descriptive approach involving 50 purposively selected respondents. Data were collected through questionnaires, interviews, and field observations, and analyzed using classical assumption tests and path Analysis with the assistance of SPSS software. The results indicate that both cost efficiency strategies and the implementation of target costing have a positive and significant effect on MSME profitability. The target costing model effectively optimizes production cost structures and enhances operational efficiency without compromising product quality. Overall, the findings demonstrate that target-based cost management serves as a strategic instrument for strengthening competitiveness and ensuring the business sustainability of coastal MSMEs.